Strategic retail management : text and international cases - Zentes, Joachim; Morschett, Dirk; Schramm-Klein, Hanna (Springer Gabler, 2017)
This book is devoted to the dynamic development of retailing. The focus is on various strategy concepts adopted by retailing companies and their implementation in practice. This is not a traditional textbook or collection of case studies; it aims to demonstrate the complex and manifold questions of retail management in the form of twenty lessons, where each lesson provides a thematic overview of key issues and illustrates them via a comprehensive case study. The examples are all internationally known retail companies, to facilitate an understanding of what is involved in strategic retail management and illustrate best practices. In the third edition, all chapters were revised and updated. Two new chapters were added to treat topics like corporate social responsibility as well as marketing communication. All case studies were replaced by new ones to reflect the most recent developments. Well-known retail companies from different countries, like Tesco, Zalando, Hugo Boss, Carrefour, Amazon, Otto Group, are now used to illustrate particular aspects of retail management. Contents Functions, Formats and Players in Retailing Strategic Marketing in Retailing Marketing Mix in Retailing Buying, Logistics and Performance Measurement Target Groups Advanced undergraduate students and graduate students majoring in Business Administration, Marketing or Management Practitioners who wish to obtain compact and practice-oriented information on current concepts The Authors Joachim Zentes is Professor Emeritus of Management and Marketing at the Saarland University, Saarbrücken, Germany. Dirk Morschett is Professor of International Management at the University of Fribourg, Switzerland. Hanna Schramm-Klein is Professor of Marketing at the University of Siegen, Germany.
Keywords: Retail trade -- Management.; Retail trade -- Management -- Case studies.; elektronické knihy; electronic books